Comparison of optical microscopy and virtual microscopy for learning histology - Simok, Anna Alicia (2018)
Background: Histology is one of the fundamentals in medical education and is part of the basic science module. Histology was traditionally taught using the optical microscope. Since early 21st century, the new virtual microscope has been integrated or has completely replaced the traditional method in various universities. This was a result of reduction in histology contact time after medical education reformation. This study aims to compare the effects of using a virtual microscope and an optical microscope for learning histology among medical students in Universiti Sains Malaysia. Methodology: One hundred and twenty medical students from 2017/2018 academic session, comprising of 53 first year students and 67 second year students were recruited. The participants were divided into two homogenous groups which were the virtual microscopy group and the optical microscopy group, using stratified random allocation. This was a one day intervention. All participants attended a lecture on ‘Histology of the Eye’ and then attended a slide demonstration. Immediately after, the two groups were divided and attended the practical session at designated laboratories for an hour. The virtual microscopy group were exposed to the virtual microscope and the optical microscopy group exposed to the optical microscope. Knowledge acquisition was measured and compared between the study groups using the postpractical assessment score, changes in assessment scores from pre to post-practical assessment and learning quotient score. Student perceptions of learning histology using respective learning tool were collected at the end of the day by administering the satisfaction survey and Intrinsic Motivation Inventory. Results: Results revealed that both study groups, the virtual microscopy group (mean difference=38.508) and the optical microscopy group (mean difference=35.079) had significant changes in assessment score, p < 0.001. However, there was no significant difference between study groups in terms of level of comprehension (post-practical assessment) and learning ability (learning quotient score). The median (IQR) of satisfaction score for the virtual microscopy group [5.00 (1)] was significantly higher compared to optical microscopy group [4.00 (2)], p=0.008. For the intrinsic motivation inventory, only the perceived competence score of virtual microscopy group was significantly higher compared to the virtual microscopy group, p=0.037. There were no significant differences between the two study groups in terms of interest, pressure and value score. Conclusion: The use of virtual microscopy as a learning tool gives students great satisfaction and perceived competence while effectively enhancing their knowledge improvement in Histology. Further investigation is needed to assess the comprehensive effect of virtual microscope in learning histology.